Forging Equality: Navigating Challenges and Seizing Opportunities for Women in Informal Employment (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Women constitute a significant portion of the labour force in India, particularly in the informal sector, where they engage in various forms of work, including wage labour, piece-rate work, casual labour, and paid family labour. This article provides a comprehensive analysis of the status of women workers in the informal sector, drawing on empirical evidence and existing literature to identify critical challenges and opportunities for policy intervention.The analysis begins by examining women's economic participation in the informal sector, highlighting their diverse roles and contributions to economic production. It explores the changing employment patterns, noting the shift from traditional sectors such as agriculture towards the service sector and the implications of globalization and technological advancements on women's labour market outcomes. Despite these trends, women in the informal sector continue to face barriers to decent work, including low wages, lack of job security, and limited access to social protection.